Legislating the Meaning of Digital Currency in the Australian Income Tax Law - Allen, Christina (Thomson Reuters (Professional), 2024)
Since Bitcoin was created in 2009, the Australian tax law has slowly responded to the increasing trading in, and widespread use of, crypto-assets. In 2017 the goods and services tax (GST) legislation was amended to introduce a new concept of "digital currency", effectively exempting crypto-assets used as a means of exchange or for the provision of financial services from taxable supplies. However, the international landscape continued to evolve: El Salvador declared Bitcoin a legal tender in 2021, and the Chinese central bank issued a new digital currency in 2020. Responding to these global shifts, the Australian federal government, in 2022, proposed refining the GST definition of "digital currency" to exclude "government-issued digital currencies". Moreover, it mooted the idea of extending this amended definition to the income tax law. This article examines the proposal to insert a new definition of "digital currency" within Australian income tax law for the first time. It begins with an exploration of the foundational principles underpinning GST and income tax. Then, navigating legal and policy implications, it casts a spotlight on digital currency within the income tax paradigm. A pertinent case in point is 'Seribu Pty Ltd v Federal Commissioner of Taxation', in which the Administrative Appeals Tribunal held that Bitcoin was not a foreign currency subject to the taxation of foreign currency gains and losses under Division 775 of the 'Income Tax Assessment Act 1997' (Cth) (the forex regime). This article then examines the GST characterisation of digital currency, juxtaposing it against the meaning of money and characteristics of central bank-issued currencies. It concludes that the adoption of the GST definition of digital currency for the income tax law is logical and that the implementation of the proposal will strengthen the legal frameworks for taxing digital currencies in Australia.